PROFITABILITY ANALYSIS AND SOCIO-ECONOMIC DETERMINANTS OF MAIZE OUTPUT IN RIJAU LOCAL GOVERNMENT AREA OF NIGER STATE, NIGERIA - Abubakar, S.; Sule, B. A.; Emefesi, B. O. (Journal of Agripreneurship and Sustainable Development, 2021)
The study assessed the profitability of maize production and socio-economic determinants of maize output in Rijau Local Government Area of Niger State, Nigeria. A multi-stage sampling technique was used in selecting 120 maize farmers. Descriptive statistics was used to assess the socio-economic characteristics of the farmers, while budgetary technique was used to determine the profitability of maize production in the study area. Socio-economic determinants of maize output were assessed using multiple regression analysis. The result showed that 25.8% of the respondents had farming experience of 6 to 10 years; majority (34.2%) had non-formal education, and 46.7% were cultivating 0.1 to 2.0 hectares of land. The study further disclosed that total variable cost accounted for 96.8% (₦133,200.5) of the total cost of production and depreciation on fixed cost that represented 3.1% (₦4,246.41) of the total cost of maize production in the study area. The return per Naira invested was ₦3.47 inferring that for each naira invested, ₦2.47k was realised as profit, hence, maize production in the study area was found to be profitable. The regression analysis revealed that farm size (23.185) and household size (8.886) significantly (P≤0.01 and P≤0.05, respectively) determined the output level of maize producers in the study area. This could be an indication of non-adoption of improved farm practices. It was recommended that effort should be made in providing efficient and accessible extension service system in order to educate farmers on the importance of improved farming practices and adoption of advanced technology.